PENGEMBANGAN METODE PENILAIAN KESEHATAN HUTAN RAKYAT SENGON ( (Miq.) Barneby & J.W. Grimes) (Jurnal Penelitian Hutan Tanaman, 2015)
ABSTRACTCriteria and indicators (C&I) of forest ecosystem health in Sustainable Forest Management (SFM) were developed for natural and plantation forests, while its implementation for community forest is not applied yet. The objective ofthis research was to develop a method for assessment of the health status of sengon ( (Miq.) Falcataria moluccanaBarneby & J.W. Grimes) community forests based on ecological indicators of forest ecosystem health. Study wasperformed using Forest Health Management (FHM) cluster-plot in monoculture sengon community forests atLampung Province. The results showed that the rate of forest health in sengon community forest could be assessedusing FHM method with priority indicators were productivity, site quality, and vitality. Method development forforest health assessment in sengon community forest can use weighted values and score value from each of thepriority indicator.ABSTRAKKriteria dan indikator, khususnya kesehatan hutan untuk Pengelolaan Hutan Lestari (PHL) baru dikembangkan terhadap hutan alam dan hutan tanaman; sedangkan untuk hutan rakyat belum dikembangkan. Penelitian inibertujuan untuk mengembangkan metode penilaian kesehatan hutan rakyat sengon ( (Miq.) Falcataria moluccanaBarneby & J.W. Grimes) berbasis indikator-indikator ekologis kesehatan hutan. Studi kasus ini dilakukan padaklaster plot Forest Health Management (FHM) hutan rakyat monokultur sengon di Wilayah Provinsi Lampung.Hasil penelitian menunjukkan bahwa tingkat kesehatan hutan rakyat sengon dapat dinilai dengan menggunakan metode FHM dengan indikator prioritas adalah produktivitas, kualitas tapak, dan vitalitas. Dalam pengembanganmetode penilaian kesehatan hutan rakyat sengon dapat menggunakan nilai tertimbang dan nilai skor dari masingmasingindikatorprioritastersebut.